2019
DOI: 10.1002/glia.23759
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of reactive astrocytes exacerbates disease pathology in a model of Alzheimer's disease

Abstract: The role of astrocytes in the progression of Alzheimer's disease (AD) remains poorly understood. We assessed the consequences of ablating astrocytic proliferation in 9 months old double transgenic APP23/GFAP‐TK mice. Treatment of these mice with the antiviral agent ganciclovir conditionally ablates proliferating reactive astrocytes. The loss of proliferating astrocytes resulted in significantly increased levels of monomeric amyloid‐β (Aβ) in brain homogenates, associated with reduced enzymatic degradation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 47 publications
6
53
0
Order By: Relevance
“…In addition, reactive astrocytes are involved in phagocytic clearance of presynaptic dystrophies in AD (Gomez‐Arboledas et al, 2018). Ablation of reactive astrocytes in AD aggravates amyloid pathology and memory loss (Katsouri et al, 2020). By contrast, other studies have shown that reactive astrocytes play a deleterious role by regulating neuroinflammation or neurotransmitters in AD mouse models (Furman et al, 2012; Jo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reactive astrocytes are involved in phagocytic clearance of presynaptic dystrophies in AD (Gomez‐Arboledas et al, 2018). Ablation of reactive astrocytes in AD aggravates amyloid pathology and memory loss (Katsouri et al, 2020). By contrast, other studies have shown that reactive astrocytes play a deleterious role by regulating neuroinflammation or neurotransmitters in AD mouse models (Furman et al, 2012; Jo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I stimulates Aβ uptake by astrocytes, while inhibits it in microglia. Whereas astrocytes appear critical to determine Aβ load [68], and increased clearance of Aβ by astrocytes may result in reduced Aβ plaques [42], inhibition of Aβ uptake by microglia may also reduce plaques [69], as the role of microglial uptake of Aβ in plaque formation may be detrimental [70,71]. In accordance with a stimulatory effect of IGF-I on astrocytes, previous observations suggested that astrocyte-derived IGF-I protects neurons against Aβ toxicity through a mechanism involving its uptake [72].…”
Section: Discussionmentioning
confidence: 88%
“…IGF-I stimulates Aβ uptake by astrocytes, while inhibits it in microglia. Whereas astrocytes appear critical to determine Aβ load (56), and increased clearance of Aβ by astrocytes may result in reduced Aβ plaques (34), inhibition of Aβ uptake by microglia may also reduce plaques (57), as the role of microglial uptake of Aβ in plaque formation may be detrimental (58,59). In accordance with a stimulatory effect of IGF-I on astrocytes, previous observations suggested that astrocyte-derived IGF-I protects neurons against Aβ toxicity through a mechanism involving its uptake (60).…”
Section: Discussionmentioning
confidence: 88%